2020
DOI: 10.1002/pat.5126
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of thermal properties of Vietnam deproteinized natural rubber via graft copolymerization with styrene/acrylonitrile and diimide transfer hydrogenation

Abstract: In this study, we investigated the improvement of thermal properties of Vietnam deproteinized natural rubber (DPNR) via graft copolymerization of styrene/acrylonitrile and transfer hydrogenation. The graft copolymerization was achieved successfully in the latex stage using tert‐butyl hydroperoxide and tetraethylenepentamine as radical initiators at 30°C. The obtained graft copolymer was hydrogenated by a diimide reduction system in the presence of different copper (II) homogeneous catalysts. The effects of sty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Herein, the NR-PMMA copolymer was slightly less subjected to degradation. This result was in line with the previous reports, which modified NR with other monomers. …”
Section: Resultssupporting
confidence: 94%
“…Herein, the NR-PMMA copolymer was slightly less subjected to degradation. This result was in line with the previous reports, which modified NR with other monomers. …”
Section: Resultssupporting
confidence: 94%
“…C-H stretching vibration at -CH 2 -is expected around 1448 cm −1 and the absorption band at 1375 cm −1 is assigned to C-H asymmetry vibration of -CH 3 . In addition, the absorption band at 1244 cm −1 is attributed to vibration of C-C stretching next to C=C, which is (R 2 C=CH-R) or at cis1,4 addition position, while the peak of 836 cm −1 indicated C=C bending vibration in NR main chain (Dinsmore and Smith 1948; Kishore and (Nguyen Duy et al 2020). Furthermore, the new absorption band appeared at wavenumber 2247 cm −1 ascribed to vibration of C≡N stretching in PAN.…”
Section: Chemical Structure Study Of Dpnr-g-(ps-co-pan)mentioning
confidence: 93%
“…The results revealed that the proper monomer content was 5 phr and proper radiation dose was 300 kGy for producing UFPNR-g-PS and UFPNR-g-PAN with maintaining rather high thermal stability. Therefore, the combination of St and AN monomer to form St/AN copolymer grafting on NR backbone is expected to improve the thermal stability and solvent resistance of NR and probably the compatibility with various polymer matrices having different polarity (Angnanon et al 2011 ; Dung et al 2017 ; Fukushima et al 1988 ; Indah Sari et al 2020 ; Nguyen Duy et al 2020 ; Nguyen et al 2019 ; Prasassarakich et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…exhibited TGA thermograms of virgin NR and UFPNR-g-(PS-co-PAN) at various radiation doses. Td5 of grafted NR was found to be higher than virgin NR due to the presence of PS-co-PAN, besides the stable aromatic rings in PS may prevent the formation of macroradicals in NR structure when exposed to heat [7,8].…”
Section: Effect Of Radiation Doses On Thermal Stability Of Ufpnrmentioning
confidence: 96%
“…The maximum value for the highest Conv and GE were achieved at weight ratio of 80/20 percentage by weight of ST/AN. Since, ST has similar polarity to polyisoprene in NR, which has higher reactivity to firstly react with polyisoprenyl macroradicals capable of further copolymerizing with AN monomer [4,7]. As the grafting on natural rubber can permanently retain the modified surface of NR particles by reducing the tackiness between particles.…”
Section: Experimental Effect Of St/an Contents On Monomer Conversion ...mentioning
confidence: 99%